Impaired decidualization of human endometrial stromal cells from women with adenomyosis. Issue 5 (2nd February 2021) - Peng, Yaoming; Jin, Zhixing; Liu, Haiou; Xu, Congjian
Abstract: Differentiation of endometrial stromal cells (ESCs) into secretory decidualized cells (dESCs) is essential for embryo implantation. Adenomyosis is a common benign gynecological disease that causes infertility. However, whether adenomyosis affects decidualization of human ESCs is elusive. Primary eutopic ESCs were obtained from patients with adenomyosis ( n = 9) and women with nonendometrial diseases ( n = 12). We determined the capacity of decidualization of human ESCs by qRT-PCR, Edu proliferation assay, cytokine array, and ELISA assay. We found that the expression of decidualization markers (IGFBP1 and PRL) in ESCs of adenomyosis was reduced, concomitant with increased cell proliferation. Differential secretion of cytokines in dESCs, including CXCL1/2/3, IL-6, IL-8, MCP-1, VEGF-A, MIP-3α, OPN, SDF-1α, HGF, and MMP-9, was observed between adenomyosis and nonadenomyosis. Moreover, the expression of decidualization regulators (HOXA10 at both mRNA and protein levels, FOXO1, KLF5, CEBPB, and HAND2 at mRNA levels) in the eutopic endometrium of adenomyosis was lower than that of nonadenomyosis. We propose that ESCs from adenomyosis have defected ability to full decidualization, which may lead to a nonreceptive endometrium. Abstract : The endometrial stromal cells of adenomyosis exhibit an aberrant decidualization response, accompanied by changes in the secretion of cytokines and matrix metalloproteinases, which may cause an unreceptive endometrium.